Development of the Regional Management of the Economy in East-Central Europe - Horváth, Gyula (Discussion Papers, 1987)
The factors hindering extensive economic development were of necessity generated in most European socialist countries by the initial advantages of an intensive industrialization. The well-known challenges of the 1970s which marked a watershed in the economy, were met in the socialist countries by an accelerated intensification of the economy. The structural transformation of the economy played an important role in these changes almost everywhere. It has gradually become self-evident that the pattern and rate of economic growth will be determined by the inner structural changes. Moreover, the spatial structure will become a major determining factor in the dynamics of the economy. Thus, the connection between economic growth and regional structure has been put into a new light, due to a slow-down in the economic processes. This study provides an overview of the development of regional management in East-Central Europe from the socialist era which had initially been characterized by the dominance of sectoral management. The first part of the study illustrates the failure and negative consequences of the hierarchic sectoral management system and introduces the reader into the reform attempts assigning a key-role to economic-administrative regions. It soon became obvious, however, that these administrative regions were far from being economic regions, planning done by economic councils could not be identified with regional planning. The second major part of the study introduces the spatial frameworks of society and the economy in the various countries, with a particular focus on the system of economic regions and social economic regionalization. The fourth section is consecrated to factors influencing the development of regional economic management in one particular country. The author seeks to reveal the meaning of decentralization in a socialist-type economy on the basis of the Hungarian experience.